Khazari Islamic relations and the position of Byzantium - Zoukar, Suhail; laika, Nadeem khalil (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
The Khazars played an important role in the Middle Ages with the Byzantines, Muslims and many contemporary peoples at the time, and increased their breadth at the expense of their neighbors, until they managed to form a strong military and economic state, taking advantage of its strategic place between the Black Sea and the Caspian Sea, entered into friendly relations with the Byzantines and allied with them In confronting the Islamic threat, the Khazar kingdom enjoyed religious and political independence despite its alliance with the Byzantines, embraced Judaism, and managed to halt Islamic expansion towards the West. شغل الخزر دوراً هاماً في العصور الوسطى مع البيزنطيين والمسلمين والعديد من الشعوب المعاصرة في ذلك الوقت، وزادت من اتساعها على حساب جيرانها، حتى تمكنت من تشكيل دولة قوية عسكرياً واقتصادياً مستغلة مكانها الاستراتيجي بين البحر الأسود وبحر قزوين، دخلت في علاقات ودية مع البيزنطيين وتحالفت معهم في التصدي للخطر الإسلامي، وتمتعت مملكة الخزر باستقلال ديني وسياسي على الرغم من تحالفها مع البيزنطيين، واعتنقت الديانة اليهودية، وتمكنت من إيقاف التوسع الإسلامي باتجاه الغرب الأوربي.